Peran Sumber Daya Manusia Dinas Kepemudaan, Olahraga dan Pariwisata dalam Pengembangan Pariwisata di Kabupaten Hulu Sungai Utara - Irawanto, I; Marhamah, Siti; Budihantho, Moh Heru; Silam, Muhammad Mochtar Mandala (Administraus, 2024)
This research discusses the role of human resources at the Youth, Sports and Tourism Department in tourism development in North Hulu Sungai Regency. The aim of this research is to determine and analyze the role of human resources at the Youth, Sports and Tourism Department in tourism development in North Hulu Sungai Regency as well as inhibiting and encouraging factors.This type of research is qualitative research. This research uses observation techniques, so the data source is called informants, with 5 informants taken from employees of the Youth, Sports and Tourism Department in Tourism Development and members of North Hulu Sungai Regency DPRD Commission II. The data mining technique that the author carried out was by means of free interviews with respondents and informants to complement the data extracted through other techniques. Based on the research results, firstly, the progress of implementers has not been optimal due to the lack of human resources in the tourism sector. Secondly, the development of the implementer is optimal, where the implementer always monitors and directs it so that tourism results are better and have a good impact. Thirdly, implementing information is not yet optimal due to the unpreparedness of the parties behind the scenes who should be responsible for improving and adding information about tourist destinations. The four implementing targets are optimal, which requires the availability of quality tourism packages with international standards. The five implementing pressures are not yet optimal because the budget from the region is not large so that the development carried out does not go according to plan. Sixth, handling the process is not yet optimal due to the lack of personnel in this field and education is still minimal and employees in this field are not vocationally qualified. Seventh, information about tourist destinations and tourism activities is not up to date. The eight actions in tourism development are always monitoring and directing. Ninth, decision making pressure for implementing tourism development is still lacking where the budget is still minimal. Keywords: Role, Tourism Development, Youth, Sports and Tourism Services in Tourism Development in North Hulu Sungai Regency ABSTRAK Tujuan dari penelitian ini adalah untuk mengetahui dan menganalisis Peran Sumber Daya Manusia Dinas Kepemudaan, Olahraga dan Pariwisata Dalam Pengembangan Pariwisata di Kabupaten Hulu Sungai Utara serta faktor penghambat dan faktor pendorong. Penelitian ini mengunakan metode penelitian ini adalah penelitian kualitatif. Penelitian ini menggunakan teknik observasi maka sumber data disebut informan, dengan informan 5 orang yang diambil dari pegawai Dinas Kepemudaan, Olahraga dan Pariwisata Dalam Pengembangan Pariwisata dan anggota DPRD Komisi II Kabupaten Hulu Sungai Utara. teknik penggalian data yang penulis lakukan dengan cara wawancara bebas pada responden dan informan untuk melengkapi data yang digali melalui teknik lainnya. Hasil penelitian ini hasil penelitian bahwa Pertama kemajuan pelaksana belum optimal yang mana kurangnya sumber daya manusia yang ada pada Bidang Pariwisata. Kedua pengembangan pelaksana sudah optimal yang mana pelaksana selalu memantau dan mengarahkan agar dalam hasil wisata lebih baik serta memberi dampak yang baik. Ketiga informasi pelaksana belum optimal karena ketidaksiapan pihak-pihak dibalik layar yang seharusnya bertanggung jawab terhadap perbaikan, penambahan informasi-informasi tentang destinasi wisata. Keempat sasaran pelaksana sudah optimal yang mana menghendaki tersedianya paket wisata berkualitas dengan standar internasional. Kelima tekanan pelaksana belum optimal karena angaran dari daerah tersebut tidak banyak sehingga dalam pengembangan yang dilaksanakan tidak berjalan sesuai dengan perencanaan. Keenam menangani proses belum optimal karena kurangnya personel yang ada pada bidang tersebut serta pendidikan yang masih minim dan pegawai pada Bidang tersebut tidak pada kejuruannya. Ketujuh informasi tentang destinasi wisata dan kegiatan kepariwisataan tidak up to date. Kedelapan tindakan dalam pengembangan pariwisata pelaksana selalu memantau dan mengarahkan. Kesembilan pengambilan keputusan tekanan pelaksanaan pengembangan pariwisata masih kurang dimana anggaran yang masih minim. Kata Kunci: Peran, Pengembangan Pariwisata, Dinas Kepemudaan, Olahraga dan Pariwisata Dalam Pengembangan Pariwisata di Kabupaten Hulu Sungai Utara